2017
DOI: 10.1038/nrmicro.2017.45
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to zoonotic spillover

Abstract: Zoonotic spillover, which is the transmission of a pathogen from a vertebrate animal to a human, presents a global public health burden but is a poorly understood phenomenon. Zoonotic spillover requires several factors to align, including the ecological, epidemiological and behavioural determinants of pathogen exposure, and the within-human factors that affect susceptibility to infection. In this Opinion article, we propose a synthetic framework for animal-to-human transmission that integrates the relevant mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
893
1
32

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 871 publications
(1,010 citation statements)
references
References 120 publications
(168 reference statements)
10
893
1
32
Order By: Relevance
“…This is especially true for the cases we present of pathogens moving between the urban matrix and wildlands. The detailed synthesis presented by Plowright et al (2017) is exactly the kind of analysis required for the (non-pathogen) factors we propose in our framework. Thus, the framework as proposed by Plowright et al (2017) is nested within the larger framework of ecological spillover, especially as relates to the factors identified that precede human exposure to pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is especially true for the cases we present of pathogens moving between the urban matrix and wildlands. The detailed synthesis presented by Plowright et al (2017) is exactly the kind of analysis required for the (non-pathogen) factors we propose in our framework. Thus, the framework as proposed by Plowright et al (2017) is nested within the larger framework of ecological spillover, especially as relates to the factors identified that precede human exposure to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Plowright et al (2017), proposed a detailed synthetic framework for assessing zoonotic spillover potential (animal-to-human transmission). This framework incorporates the rich research history in epidemiology and disease ecology into an interacting hierarchy of spillover pathways and bottlenecks to understand gaps in knowledge, determine the parameters of risk analysis, examine potential points of intervention and control, and develop mathematical models for zoonotic spillover, Ecological spillover dynamics of organisms from urban to natural landscapes | 7 among other goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between-species transmission of infection in multi-host disease systems remains poorly understood, despite representing a potentially important opportunity for disease control (Plowright et al, 2017;Webster et al, 2017). The behaviours that might result in transmission of infections between species are often rare (Viana et al, 2014), with successful transfer and establishment of the pathogen in a new host being rarer still (Woolhouse et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This distinction can be particularly important when direct interactions among potential hosts are rare, which is likely to be the case for between-species transmission (Viana et al, 2014). Identifying the relative importance of direct and indirect transmission, and the behaviours involved, are therefore likely to be important prerequisites to the development of effective disease management strategies (Plowright et al, 2017;Webster et al, 2017).…”
Section: Introductionmentioning
confidence: 99%